2012
DOI: 10.1590/s1517-83822012000100023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance and representation of toxigenic and non-toxigenic Clostridium difficile cultivated from stool samples of hospitalized patients

Abstract: The aim of this study was to fortify the clinical importance and representation of toxigenic and non-toxigenic Clostridium difficile isolated from stool samples of hospitalized patients. This survey included 80 hospitalized patients with diarrhea and positive findings of Clostridium difficile in stool samples, and 100 hospitalized patients with formed stool as a control group.Bacteriological examination of a stool samples was conducted using standard microbiological methods. Stool sample were inoculated direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Although C. difficile toxins are considered crucial for disease development, previous studies have reported that nontoxigenic C. difficile is also present in the stool samples of hospitalized patients with persistent diarrhea (38). Our results indicate that regardless of purified SLPs or direct infection of C. difficile to cells, similar trends were observed, which demonstrated that SLPs and lipid rafts are important for the C. difficile-induced inflammasome activation.…”
Section: Discussionsupporting
confidence: 76%
“…Although C. difficile toxins are considered crucial for disease development, previous studies have reported that nontoxigenic C. difficile is also present in the stool samples of hospitalized patients with persistent diarrhea (38). Our results indicate that regardless of purified SLPs or direct infection of C. difficile to cells, similar trends were observed, which demonstrated that SLPs and lipid rafts are important for the C. difficile-induced inflammasome activation.…”
Section: Discussionsupporting
confidence: 76%
“…In the period 2005-2010 at the Public Health Institute in Niš, the first study was done about the prevalence of toxigenic and non-toxigenic strains (1,15,16) and C. difficile carrier status (17) in patients and people from the territory of Serbia. The results of the study showed the predominance of strains producing both toxins (A+B+), but also the presence of strains that produce toxin B only (A-B+), which requires the use of microbiological diagnostic tests to reveal and confirm both toxins in order to avoid false negative results (16).…”
Section: Microbiological Diagnosis Of Cdad In Serbiamentioning
confidence: 99%
“…Since 2009, CDI has been recognized as an increasing nosocomial infection in healthcare facilities in Serbia [11][12][13]. Serbia has 7,164,000 inhabitants and 67 acute care hospitals.…”
Section: Introductionmentioning
confidence: 99%